The Manaus industrial hub and the preservation of the standing amazon rainforest - Silva , Michele Lins Aracaty e (Seven Editora, 2023)
The socioeconomic importance of the Manaus Free Trade Zone model and its longevity of 56 uninterrupted years is an unquestionable reality, but the discussion about the contribution of the model in the environmental sphere has long been raised. To this end, we aim to analyze the Manaus Free Trade Zone model as a regional development policy and an instrument of environmental protection. Methodologically, it is a qualitative, exploratory, and descriptive, bibliographic and documental research with content analysis. Amazonas preserves a vast region made up of conservation units, indigenous lands and primary public forests (only 1% of the state's area is under pressure and with deforestation rates). The predominance of an industrial model, the supply of jobs in the manufacturing industry, population concentration, transport logistics, waterway transport, as well as the presence of conservation units and indigenous lands contribute directly and indirectly to the low rates of deforestation in Amazonas. If the main regional development model called the Manaus Free Trade Zone were to be extinguished, we would have a collapse in the entire macroeconomic scenario, which would stimulate a resumption of the process of exploitation of natural resources, mining, cattle ranching, illegal logging, as well as deforestation throughout the region. DOI:https://doi.org/10.56238/sevened2023.004-013